Eco-Friendly Ground Remediation: Assessing the Efficacy of Plant Fibers, Green Stones, and Antibacterial Agent - Firoozi, Ali; Firoozi, Ali Asghar (New Environmentally-Friendly Materials, 2023)
Ground contamination poses significant environmental and health challenges globally. Traditional remediation methods, while effective, have often resulted in secondary environmental issues. In light of this, there has been a distinct shift towards more sustainable solutions. This study delves into the potential of three environmentally friendly materials, namely plant fibers, green stones, and anti-bacterial substances, as viable tools for ground remediation. Simulated scenarios, representing industrial, agricultural, and urban landfill contaminations, were employed to assess the efficacy of these materials. Results suggest that each material has a unique potential to address specific contamination types, underpinning their value in a comprehensive, eco-conscious ground remediation strategy.